2011
DOI: 10.1177/0009922811419027
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Interactive Web-Based Module on Residents’ Knowledge and Clinical Practice of Injury Prevention

Abstract: The noninteractive module was more effective in promoting knowledge acquisition. Residents successfully demonstrated knowledge retention with completion of either module. The modules were insufficient to change clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In contrast, Sangvai and colleagues demonstrated that while an internet web-based module on childhood injury prevention improved performance on post-tests given immediately and 7 months following completion of the module, the module did not impact clinical practice as assessed by videotaped clinical visits. [18] Similar findings were observed in a randomized trial comparing internet-based versus paper-based educational exercises focused on geriatric clinical issues in which neither modality improved clinical practice [19]. These recent studies highlight the difficulty in improving clinical practice and underscore the need for improved educational interventions.…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, Sangvai and colleagues demonstrated that while an internet web-based module on childhood injury prevention improved performance on post-tests given immediately and 7 months following completion of the module, the module did not impact clinical practice as assessed by videotaped clinical visits. [18] Similar findings were observed in a randomized trial comparing internet-based versus paper-based educational exercises focused on geriatric clinical issues in which neither modality improved clinical practice [19]. These recent studies highlight the difficulty in improving clinical practice and underscore the need for improved educational interventions.…”
Section: Discussionsupporting
confidence: 55%
“…A majority of programmes, 24 of the 44, were designed for paediatric injury prevention: 14 programmes were designed to be used by children,24–40 7 programmes targeted parents,41–50 2 programmes provided anticipatory guidance training for paediatricians,51 52 and 1 programme was designed for preschool staff 53. Programmes designed for use by children primarily covered pedestrian safety,24 25 30 32 34–36 38–40 fire safety24 29 37 or dog-bite prevention27 28 33 and included seven software programmes,24–31 two internet programmes,32 33 and five programmes using virtual-reality settings 34–40.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently addressed safety behaviour was fire and burn safety, incorporated into 16 of the studies—three programmes for children,24 29 37 seven programmes for parents,41 42 44–50 and six programmes for clinicians or caregivers 51 54–58. Each of the seven programmes designed for parents offered education about smoke alarms among a list of other injury-prevention topics.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge retention is a more difficult outcome to study and may cause distress in patients. Studies in the literature looking at knowledge retention have been on medical students and residents . This study was therefore embarked upon to ascertain the short‐term effects on hospital stay, pain and nausea scores.…”
Section: Discussionmentioning
confidence: 99%